Pengaruh Suasana Toko dan Kualitas Produk terhadap Kepuasan Pelanggan melalui Keputusan Pembelian di Mcdonald’s Buaran - Mayndra Penthino Monfort Rere; Rivera Pantro Sukma (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This research was conducted to determine the effect of store atmosphere influence and product quality on customer satisfaction through purchase decisions at Mcdonald's Buaran. The participants of this study were customers who had visited McDonald's Buaran on more than two occasions. The technique employed for sampling in this study was purposive sampling of 150 respondents. Methods of data collection using questionnaires distributed to respondents. Meanwhile, hypothesis testing includes path analysis with the help of SmartPLS 3.0. The results of this study are that store atmosphere has a positive and significant effectt on purchasing decisions; product quality has a positive and significant effect on purchasing decisions; store atmosphere has a positive and significant effect on customer satisfaction; purchasing decisions have a positive and significant effect t on customer satisfaction, store atmosphere has a positive and significant effect on customer satisfaction through purchasing decisions; and product quality has a positive and significant effect on customer satisfaction through purchasing decisions; as for product quality has no significant effect on customer’s satisfaction. The result of the coefficient of determination purchasing decision is 28.3% and customer satisfaction is 50.6%.